Nitric Oxide Synthase Regulates Gut Microbiota Homeostasis by ERK-NF-κB Pathway in Shrimp - Hong, Pan-Pan; Zhu, Xiao-Xu; Yuan, Wen-Jie; Niu, Guo-Juan; Wang, Jin-Xing (Frontiers in Immunology, 2021)
The gut microbiota is a complex group of microorganisms that is not only closely related to intestinal immunity, but also affects the whole body's immune system. Antimicrobial peptides and reactive oxygen species participate in the regulation of gut microbiota homeostasis in invertebrates. However, it is unclear whether nitric oxide (NO), as a key mediator of immunity that plays important roles in anti-pathogen activity and immune regulation, participates in the regulation of gut microbiota homeostasis. In this study, we identified a nitric oxide synthase (NOS) responsible for NO production in the shrimp Marsupenaeus japonicus. The expression of Nos and the NO concentration in the gastrointestinal tract were increased in shrimp orally infected with Vibrio anguillarum. After RNA interference of Nos and treatment with an inhibitor of NOS, L-NMMA, NO production decreased and the gut bacterial abundance increased significantly in shrimp. Treatment with the NO donor, Sodium nitroprusside, increased the NO level and reduced the bacterial load significantly in the shrimp gastrointestinal tract. Mechanistically, V. anguillarum infection increased NO level via upregulation of NOS, and induced phosphorylation of ERK. The activated ERK phosphorylated the NF-B like transcription factor, Dorsal, which caused translocation of Dorsal into the nucleus and resulted in increased expression of antimicrobial peptides responsible for bacterial clearance. In summary, NOS-produced NO regulates intestinal microbiota homeostasis by promoting antimicrobial peptide expression via the ERK-Dorsal pathway as a signaling molecule or by directly killing bacteria as an effector molecule in shrimp.